High-moisture or dry corn, roughage sources, and protein supplements for short-fed finishing steers - Young, B.; Ilg, H.; Bolsen, K. (Kansas State University. Agricultural Experiment Station, 2010)
Dry corn, stave ensiled high-moisture corn (HMC), stave ensiled HMC treated with urea, and Harvestore ensiled HMC were evaluated in a steer finishing trial. Alfalfa hay and corn silage were the roughages and soybean meal or urea, the nitrogen sources. There were no differences in steer performance for corn treatments, but steer performance was significantly improved when alfalfa hay rather than corn silage was the roughage. Urea supplements significantly depressed steer performance compared with soybean meal additions; a combination of urea and soybean meal gave intermediate performance.
Keywords: Beef; Corn; Finishing steers; Performance; Protein